HUBUNGAN DUKUNGAN KELUARGA DENGAN KECEMASAN IBU DARI ANAK YANG MENDERITA BRONKOPNEUMONIA DI BKPM KOTA PEKALONGAN - Moh. Projo Angkasa; Isrofah Isrofah; Maslahatul Inayah; Indayah Dewi Tunggal (JURNAL LITBANG KOTA PEKALONGAN, 2016)
CHILDREN ARE SENSITIVE TO DISEASES SUCH AS BRONCHOPNEUMONIA. BRONCHOPNEUMONIA DISEASE REQUIRES CARE AND REGULER TREATMENT AND LONGER, SO IT CAUSE ANXIETY. MOTHER OVERCOME THE ANXIETY NEED FAMILIY SUPPORT TO PROVIDE GOOD CARE TO HER CHILDREN. THIS RESEARCH TRIED TO FIND OUT MOTHERS ANXIETY LEVEL IN CHILDREN WITH BRONCHOPNEUMONIA AT BKPM PEKALONGAN. DESIGN OF THIS RESEARCH WAS DESCRIPTIVE CORRELATIVE WITH CROSS SECTIONAL APPROACH. SAMPLES OF THIS RESEARCH WERE 118 MOTHERS OF CHILDREN WITH BRONCHOPNEUMONIA AT BKPM PEKALONGAN. THE SAMPLING TECHNIQUE USED WAS SIMPLE RANDOM SAMPLING. THE RESEARCH INSTRUMENT WAS QUESTIONNAIRE. ANALYSIS OF DATA USED CHI SQUARE. RESULT 59 PEOPLE (50%) GOT GOOD FAMILY SUPPORT AND 73 PERSONS (61,9%) DID NOT ANXIETY. THERE WAS A SIGNIFICANT CORRELATION BETWEEN FAMILY SUPPORT AND MOTHERS ANXIETY LEVEL IN CHILDREN WITH BRONCHOPNEUMONIA WITH ? VALUE 0.001. SUGGESTION NURSES SHOULD GIVE INFORMATION ABOUT THE DISEASE AND THE TREATMENT OF BRONCHOPNEUMONIA THAT THE MOTHERS ARE NOT ANXIETY ABOUT THEIR CHILDREN.